2022
DOI: 10.1172/jci.insight.159357
|View full text |Cite
|
Sign up to set email alerts
|

Senescence plays a role in myotonic dystrophy type 1

Abstract: Myotonic dystrophy type 1 (DM1; MIM #160900) is an autosomal dominant disorder, clinically characterized by progressive muscular weakness and multisystem degeneration. The broad phenotypes observed in DM1 patients resemble the appearance of an accelerated aging process. However, the molecular mechanisms underlying these phenotypes remain largely unknown. Transcriptomic analysis of fibroblasts derived from DM1 patients and healthy individuals revealed a decrease in cell cycle activity, cell division, and DNA da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 64 publications
1
12
0
Order By: Relevance
“…Quercetin and other flavonoids including fisetin have been described as senolytics, compounds that selectively induce cell death in senescent cells ( 23 ). Recent studies demonstrated that accelerated senescence, which is observed in myotonic dystrophy models, could be modulated using senolytics ( 24, 25 ). In these studies, senolytic treatment reduced key molecular markers of senescence including p16 in cellular and animal models of DM1, supporting senolytics as potential therapeutics for DM ( 24, 25 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Quercetin and other flavonoids including fisetin have been described as senolytics, compounds that selectively induce cell death in senescent cells ( 23 ). Recent studies demonstrated that accelerated senescence, which is observed in myotonic dystrophy models, could be modulated using senolytics ( 24, 25 ). In these studies, senolytic treatment reduced key molecular markers of senescence including p16 in cellular and animal models of DM1, supporting senolytics as potential therapeutics for DM ( 24, 25 ).…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies demonstrated that accelerated senescence, which is observed in myotonic dystrophy models, could be modulated using senolytics ( 24, 25 ). In these studies, senolytic treatment reduced key molecular markers of senescence including p16 in cellular and animal models of DM1, supporting senolytics as potential therapeutics for DM ( 24, 25 ). However, the effects of quercetin and/or other senolytics on key molecular hallmarks of RNA toxicity including mis-splicing were not determined ( 24, 25 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations